Empowering Civil Society in the Digital Era: Preventing Lagging Behind in the Digital Civilization - Al Iffah, Nisa (SERUNAI, 2022)
This research explores the important role of civil society empowerment in facing the increasingly advancing digital civilization. In an era where digital technology dominates every aspect of life, civil society needs to be equipped with the knowledge, skills, and resources required to fully benefit from this digital revolution. This study identifies challenges faced by civil society in the context of digital technology, including unequal access, information security, digital literacy, and ethical issues. Additionally, the research also explores strategies and solutions that can be used to empower civil society, enabling them to actively participate in the digital civilization and prevent potential lagging behind. The findings of this research provide valuable insights into how civil society can contribute to shaping an inclusive and just future digital civilization.